2020
DOI: 10.3390/microorganisms8081122
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Pollution Drives Antibiotic Resistance and Class 1 Integron Abundance in Aquatic Environments of the Bolivian Andes Impacted by Mining and Wastewater

Abstract: An increased abundance of antibiotic resistance genes (ARGs) in aquatic environments has been linked to environmental pollution. Mining polluted sites with high concentration of metals could favor the in situ coselection of ARGs, whereas wastewater discharges release fecal antibiotic resistant bacteria in the environment. To study the effect of human fecal contamination and mining pollution, water and sediment samples affected by mining activities and sewage discharges were collected from three lakes in Bolivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 61 publications
2
14
0
Order By: Relevance
“…It is known that even the discharge of treated sewage can release antibiotic-resistant bacteria, transmissible genetic elements that encode resistance, and antibiotics residue into environments [84,85]. Therefore, the emergence and dissemination of ABR has been linked to fecal pollution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that even the discharge of treated sewage can release antibiotic-resistant bacteria, transmissible genetic elements that encode resistance, and antibiotics residue into environments [84,85]. Therefore, the emergence and dissemination of ABR has been linked to fecal pollution.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, resistance to cefalexin (46%), ampicillin (40%), amoxicillin + clavulanic acid (42%), streptomycin (34%), and tetracycline (35%), were the highest (Figure 4). These antibiotics are considered clinically and agriculturally important, increasing the risk of complicated infections in swimmers, consumers of produce irrigated with contaminated waters, and livestock that might use these waters [85,92]. Resistance to carbapenems was low and only identified in three isolates from the North, specifically in Zgharta and Oyoun el Samak rivers (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the risk of developing ABR microbes has increased. The ABR pathogens excrete through human and animal stools can accumulate in the natural ecosystems and spread throughout the environment ( Walsh et al., 2011 ; Karkman et al., 2019 ; Agramont et al., 2020 ). It is suggested that public health interventions should be implemented to improve water and food quality in the emerging economies and better sewage disposal.…”
Section: Global Distribution Of Abr Via One Healthmentioning
confidence: 99%
“…Nevertheless, insufficient and failing infrastructure, including sanitation infrastructure, remains a major obstacle to achieving this goal, a problem shared by many other low‐ and medium‐income countries (Asem‐Hiablie et al, 2013; Egbi et al, 2020; Gwenzi & Chaukura, 2018). Rural communities in Ghana rely on a patchwork of latrines, household septic systems, and underperforming sewage‐treatment facilities for the treatment of human waste (Egbi et al, 2020), all serving as potential sources of antibiotic‐resistant microorganisms and antibiotic‐resistance genes (ARGs; Agramont et al, 2020; Ho et al, 2021; Thongsamer et al, 2021; Vikesland et al, 2019). Hormones (Aneck‐Hahn et al, 2009) and pharmaceuticals (see review by Fekadu et al, 2019) also end up in surface water.…”
Section: Introductionmentioning
confidence: 99%